Preparation of Sb-doped ZnO nanostructures and studies on some of their properties - Ilican, Saliha; Caglar, Yasemin; Caglar, Mujdat; Yakuphanoğlu, Fahrettin; Cui, Jingbiao (Elsevier Science Bv, 2008)
Sb-doped ZnO nanostructures have been deposited onto glass substrates by a sol-gel method. The structural, optical and electrical properties of the Sb-doped ZnO films were characterized by various techniques including scanning electron microscopy, X-ray diffraction. UV-vis absorption, photoluminescence, and electrical transport measurements. The surface morphology of the nanostructure films is found to depend on the concentration of Sb in the source materials. Band-edge emission at 376 nm and a broad defect band around 530 nm were shown in the photoluminescence spectra. An emission band at 400 nm was also observed, which is likely associated with the interstitial Zn in ZnO. The current-voltage characteristics of the films indicate a non-linear behavior. The conductivity type of the films changes from n-type to p-type with increasing Sb-dopant. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Nanostructure; Sol-gel spin coating; Sb-doped zinc oxide; Photoluminescence; Electrical transport properties